Wear-resistant epoxy floor coating and preparation method thereof
By modifying the acid anhydride silicane coupling agent on the surface of nanoparticles, the problem of easily wear the epoxy floor coatings in the water environment and improve the dispersability of nanoparticles in epoxy resin, thereby improving the strength of the material And wear resistance.
Patent Information
- Application Number
- CN202411684838.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-01-28
AI Technical Summary
Existing epoxy floor coatings are prone to wear and wear when there is water, and nanoparticles are difficult to disperse evenly in epoxy resin, resulting in a degradation of material performance.
The nanoprocol surface is modified to use the acidic anhydrial anhydrial sirrioma coupling agent. The modified nanoparticles maintain a high amount of addition in the epoxy system and are not easy to reunite to improve its decentralized stability in epoxy resin.
It significantly improves the strength, abrasion resistance and toughness of the epoxy floor, and ensure its performance in high mechanical load and water environment.
Smart Images

Figure BDA0005149173350000051 
Figure BDA0005149173350000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of epoxy coatings, and more specifically, to a wear-resistant epoxy floor coating and a preparation method thereof. Background Art
[0002] Epoxy floor coating is a high-strength, wear-resistant and beautiful floor coating. It is widely used in machinery manufacturing plants, hardware factories, automobile factories and aerospace bases because of its advantages such as seamless, solid texture, corrosion resistance, dustproof, easy maintenance and low maintenance cost.
[0003] Because heavy machinery and equipment need to be parked and transported in machinery manufacturing plants, hardware factories, automobile factories, aerospace bases and other places, epoxy floors need to have greater mechanical strength, toughness and wear resistance to withstand the pressure and impact of heavy machinery and equipment. But in fact, the wear resistance of ordinary epoxy floors is not ideal, and they are more prone to scratches and wear in water. After introducing inorganic fillers into epoxy coatings, these shortcomings can be effectively overcome and the wear resistance of coatings can be significantly increased. These inorganic fillers include corundum, silicon powder, metal oxide nanoparticles, etc. However, the amount of the above-mentioned inorganic fillers is limited, and their particle size needs to be strictly controlled. Once the amount added is too high or the particle size is too small, it is easy to agglomerate in the epoxy system, resulting in stress concentration in the epoxy floor, easy cracking, and mechanical properties instead of increasing.
[0004] Inorganic fillers, such as nano-silica and metal oxide nanoparticles, have the characteristics of high specific surface area, porosity, and high surface energy, which can improve the interfacial bonding force between the particles and the resin matrix. However, nanoparticles are very easy to agglomerate in epoxy resin and are difficult to disperse evenly and stably. There are three main reasons for this: 1) The nanoparticles themselves have a high specific surface area, which makes them tend to form agglomerates under the action of van der Waals forces and Coulomb forces; 2) The surface of nanoparticles is highly hydrophilic and has poor interfacial wettability with the epoxy matrix, so they tend to form agglomerates to reduce the surface energy of the system; 3) The high viscosity of the epoxy matrix further increases the difficulty of dispersing nanoparticles.
[0005] The dispersion state of nanoparticles will have a decisive influence on the performance of modified epoxy resin: on the one hand, agglomeration leads to an increase in the particle size of nanoparticles and a decrease in the specific surface area, which greatly reduces the size effect of nanoparticles and the modification effect; on the other hand, larger agglomerates may behave like defects in the mechanical and electrical behavior of epoxy resin, which will lead to a decrease in material performance. Therefore, achieving good dispersion of nanoparticles in epoxy resin is an important prerequisite for preparing epoxy resin with stable and superior performance. Summary of the invention
[0006] In order to solve the above technical problems, the present application provides a wear-resistant epoxy floor coating and a preparation method thereof, and specifically provides a homemade anhydride-type silane coupling agent to modify the surface of nanoparticles, so that the inorganic filler can maintain a high addition amount in the epoxy system without being easily agglomerated, and the prepared epoxy floor has high strength, wear resistance and toughness.
[0007] In the first aspect, the present application provides a wear-resistant epoxy floor coating, which adopts the following technical solution:
[0008] A wear-resistant epoxy floor coating, comprising component A and component B which are independently packaged and used in a weight ratio of 1:1, wherein the component A comprises the following components in parts by weight: 100 parts of epoxy resin, 10-50 parts of modified filler, 1-15 parts of active diluent, 10-30 parts of water, and 0-10 parts of additives; the component B comprises the following components in parts by weight: 50 parts of curing agent;
[0009] The modified filler is prepared by surface modification of the filler with an anhydride type silane coupling agent. The filler is an inorganic nanoparticle, specifically nano-silicon dioxide or nano-alumina. The general structural formula of the anhydride type silane coupling agent is YSi(OR)3, wherein Y is an anhydride group and R is an alkyl group.
[0010] Preferably, in the general structural formula of the anhydride-type silane coupling agent, Y is a maleic anhydride group, and the anhydride-type silane coupling agent is obtained by a pericyclic reaction of maleic anhydride and α-alkenyl silane.
[0011] The α-alkenyl silane includes but is not limited to acryltrimethoxysilane, acryltriethoxysilane, isobutylenyltrimethylsilane, 5-hexenyltrimethoxysilane and the like.
[0012] The specific preparation steps of the anhydride type silane coupling agent are: mixing maleic anhydride and α-alkenyl silane, maintaining the mixture at a certain reaction temperature for a certain time, and then separating and purifying the mixture to obtain the anhydride type silane coupling agent.
[0013] Preferably, during the preparation of the anhydride type silane coupling agent, a polymerization inhibitor may be added to prevent the reactants with double bonds from forming free radicals and undergoing free radical polymerization. Further, the polymerization inhibitor may be selected from hydroquinone and / or p-hydroxyanisole.
[0014] Preferably, during the preparation of the anhydride-type silane coupling agent, the heating reaction temperature is 180-200° C., and the heating reaction time is 8-16 h.
[0015] The surface of nanoparticles contains a large number of hydroxyl groups, which are easy to form hydrogen bonds, resulting in mutual attraction and agglomeration between particles. However, at the same time, these hydroxyl groups are also targets for chemical surface modification. When an anhydride-type silane coupling agent is used to modify the surface of nanoparticles, the silane group combines with the hydroxyl groups on the surface of the particles, thereby fixing the coupling agent molecules on the surface of the nanoparticles, and the anhydride groups in the coupling agent molecules become new groups on the surface of the nanoparticles. Therefore, the obtained modified nanoparticles not only have improved dispersion stability, but also the anhydride groups on the surface of the modified nanoparticles can react with the epoxy groups of the epoxy resin to participate in the curing of the epoxy resin.
[0016] The specific preparation steps of the modified filler are: using water as a solvent to prepare a nanoparticle dispersion, mixing the nanoparticle dispersion with an anhydride type silane coupling agent, heating and reacting for a period of time, and then separating and purifying to obtain the modified filler.
[0017] Preferably, in the preparation process of the modified filler, the amount of anhydride type silane coupling agent used is 1-3wt% of the nanoparticles.
[0018] Preferably, during the preparation of the modified filler, the heating temperature is 60-80° C. and the heating reaction time is 8-16 h.
[0019] Preferably, during the preparation of the modified filler, the crude product of the reaction can be directly freed of solvent to obtain the finished product; or, it can be first concentrated and then purified using a dialysis bag, and finally evaporated to dryness by rotary evaporation to obtain the finished product.
[0020] The above-mentioned method of directly removing the solvent, the modified filler obtained contains excess unreacted anhydride silane coupling agent, and the excess unreacted anhydride silane coupling agent can also directly participate in the curing reaction of the epoxy resin. The flexible long side chains contained in the anhydride silane coupling agent can reduce the crosslinking density or crystallinity of the curing system, thereby improving the toughness of the epoxy system; and the method of removing the excess unreacted anhydride silane coupling agent with a dialysis bag, the modified filler obtained is solid, suitable for industrial production, transportation and use, and also has a high commercial application prospect.
[0021] Preferably, the epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, aliphatic glycidyl ether epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin, alicyclic epoxy resin, cyanuric acid triglycidyl epoxy resin, and hydantoin epoxy resin.
[0022] Furthermore, the epoxy resin is a mixture of a high molecular weight solid epoxy resin and a low molecular weight liquid epoxy resin, wherein the high molecular weight solid epoxy resin is E-20, E-12, E-03, E-06, etc., and the low molecular weight liquid epoxy resin is E-44, E-42, E-51, E-54, etc.
[0023] Preferably, the epoxy resin of the present application adopts a combination of E-12 and E-44 to have good coating leveling, high hardness and high toughness of the paint film. More preferably, the weight ratio of E-12 to E-44 is 1:(2-3).
[0024] Preferably, the active diluent is at least one of benzyl glycidyl ether, 1,4-butanediol diglycidyl ether, cyclohexanediol diglycidyl ether, resorcinol diglycidyl ether, o-cresyl glycidyl ether, cyclopentanediol diglycidyl ether, trimethylol triglycidyl ether, polypropylene glycol diglycidyl ether and ethylene glycol diglyceryl ether.
[0025] Furthermore, in the component A, the additives include but are not limited to leveling agents, defoaming agents, pigments and other auxiliary agents, and the additives can be added one by one or in combination.
[0026] This application has no special requirements on the type of leveling agent. The leveling agent can be selected from any one of polyacrylic acid, modified polysiloxane and modified acrylate leveling agents, such as the leveling agent products produced by BYK and AFCONA, and specific products include BYK-306, BYK-333, BYK-323, AFCONS-7370, AFCONS-7371, etc.
[0027] The defoamer can be a silicone defoamer or an acrylic polymer, such as the defoamer products produced by BYK and AFCONA, and specific products include BYK-054, BYK-085, BYK-A 515, AFCONA-7200, AFCONA-7201, AFCONA-2045, etc.
[0028] The pigment may be an organic pigment or an inorganic inert pigment, wherein the organic pigment includes phthalocyanine blue, phthalocyanine green, light-fast yellow, etc., and the inorganic inert pigment includes titanium dioxide, carbon black, iron oxide red, iron oxide black, etc.
[0029] Preferably, in the B component, the curing agent is selected from at least one of an amine curing agent and an acid anhydride curing agent.
[0030] Preferably, the B component further comprises a curing accelerator, which is selected from at least one of a phenolic accelerator, an imidazole accelerator, an amine accelerator, and a Lewis acid accelerator. Among them, phenolic accelerators include phenol, resorcinol, nonylphenol, bisphenol A, and 2,4,6-tris(dimethylaminomethyl)phenol, etc., amine accelerators include o-hydroxybenzyldimethylamine, triethylamine, triethanolamine, benzyldimethylamine, and alkyltrimethylammonium bromide salts, etc., imidazole accelerators include 2-methylimidazole and 2-phenylimidazole, etc., and Lewis acid accelerators include BF3, SnCl4, AlCl3, FeCl3, TiCl4, and ZnCl2, etc.
[0031] In a second aspect, the present application provides a method for preparing an epoxy floor coating, using the following technical solution:
[0032] A preparation method of an epoxy floor coating. During the preparation, components A and B are prepared and packaged independently. When used, they are mixed and stirred evenly in a weight ratio of 1:1. The preparation method of component A is as follows: epoxy resin, modified filler, active diluent, water and additives are mixed and stirred evenly to obtain the coating.
[0033] In summary, this application has the following beneficial effects:
[0034] (1) using an anhydride type silane coupling agent to modify the surface of the nanoparticles, grafting new anhydride groups on the surface of the nanoparticles, the obtained modified nanoparticles not only have improved dispersion stability, but also the anhydride groups on the surface of the modified nanoparticles can react with the epoxy groups of the epoxy resin to participate in the curing of the epoxy resin;
[0035] (2) In the present application, the anhydride silane coupling agent can be used in excess, which can not only ensure that the hydroxyl groups on the surface of the nanoparticles are completely reacted, but also the excess anhydride silane coupling agent can directly participate in the curing reaction of the epoxy resin. The flexible long side chains contained in the anhydride silane coupling agent can reduce the crosslinking density or crystallinity of the curing system, thereby improving its toughness;
[0036] (3) The epoxy resin described in the present application adopts a combination of E-12 and E-44. The epoxy system can have excellent coating leveling, high paint film hardness, high wear resistance and high toughness. DETAILED DESCRIPTION
[0037] The present application is further described in detail below with reference to the embodiments.
[0038] Properties and sources of some raw materials used in this application:
[0039] Allyltriethoxysilane, CAS number: 2550-04-1; Isobutylenetrimethylsilane, CAS number: 18292-38-1.
[0041] The average particle size of the nano-silicon dioxide particles is 20 nm.
[0042] Epoxy resins E-12 and E-44 were purchased from Hubei Shiteng Chemical Technology Co., Ltd.
[0043] Example 1-5 Preparation of silane coupling agent
[0044] Embodiment 1 An anhydride type silane coupling agent: 107.28g (525mmol, 1.05eq.) of allyl triethoxysilane and 0.5g of p-hydroxyanisole were added to a 500mL round-bottom flask, and 49.03g (500mmol, 1.00eq.) of maleic anhydride were added in batches under stirring conditions to form a uniform suspension of the mixture, and then 14.41g (150mmol, 0.30eq.) of methanesulfonic acid was slowly added dropwise. After the addition was completed, the mixture was heated to reflux at 190°C for 10h. After cooling, 200mL of n-heptane was added, and the catalyst layer was removed by separation, and then washed three times with deionized water, washed once with saturated brine, dried over anhydrous sodium sulfate, and filtered. The obtained filtrate was subjected to reduced pressure distillation at 130°C to remove the solvent, and finally 135.48g (yield 89.6%) of the product was obtained.
[0045] The product H NMR spectrum data are:
[0046] 1 H-NMR((CD3)2CO,400MHz,ppm):5.7(t,1H),5.0(s,1H),3.82(d,6H),3.13(d,2H),3.0(t,1H),2.22(t,21H),1.21(d,9H).
[0047] Example 2 An anhydride type silane coupling agent: 64.15g (525mmol, 1.05eq.) isobutylene trimethylsilane and 0.5g p-hydroxyanisole were added to a 500mL round-bottom flask, and 49.03g (500mmol, 1.00eq.) maleic anhydride was added in batches under stirring conditions to form a uniform suspension of the mixture, and then 14.41g (150mmol, 0.30eq.) methanesulfonic acid was slowly added dropwise. After the addition was completed, the mixture was heated to reflux at 185°C for 16h. After cooling, 200mL of n-heptane was added, and the catalyst layer was separated and washed three times with deionized water, washed once with saturated brine, dried over anhydrous sodium sulfate, and filtered. The obtained filtrate was subjected to reduced pressure distillation at 130°C to remove the solvent, and finally 96.31g (yield 85.1%) of the product was obtained.
[0048] The product H NMR spectrum data are:
[0049] 1H-NMR ((CD3)2CO, 400MHz, ppm): 4.81 (d, 1H), 3.58 (s, 9H), 3.04 (t, 1H), 3.01 (d, 2H), 2.18 (d, 2H), 1.72 (s, 3H).
[0050] Example 3 An aminosilane coupling agent, chemically named aminopropyltriethoxysilane, specifically silane coupling agent KH-550.
[0051] Example 4 An epoxy silane coupling agent, chemical name is glycidyloxypropyltrimethoxysilane, specifically silane coupling agent KH-560.
[0052] Example 5 A vinyl silane coupling agent, chemical name vinyl trimethoxy silane, specifically silane coupling agent A-171.
[0053] Performance test: Modification effect of silane coupling agent on pure epoxy resin
[0054] The silane coupling agent provided in Examples 1-5 was mixed evenly with the epoxy resin E-44, and then a curing agent DDS of 50% of the mass of the epoxy resin was added, and the mixture was heated to 80°C and stirred evenly, and after degassing, it was poured into a polytetrafluoroethylene mold, and cured and molded according to the process of 80°C / 3h→150°C / 2h→175°C / 1h. Mechanical properties of the epoxy resin cured product without the addition of the silane coupling agent and the epoxy resin cured product with the addition of the silane coupling agent of each example were tested, and the test results were recorded in Table 2 below.
[0055] Table 1 Test results of mechanical properties of epoxy resin
[0056]
[0057]
[0058] It can be seen from the test results in Table 1 that when amino, epoxy, and vinyl silane coupling agents directly participate in the curing reaction of epoxy resin, the tensile strength of the obtained epoxy resin cured product is improved to a certain extent, but the impact strength is not significantly improved, especially the epoxy resin modified by aminosilane coupling agent, the impact strength after curing is not only not improved, but it is reduced to a certain extent. This may be because the silane coupling agent increases the curing crosslinking degree of epoxy resin, so that its tensile strength is improved, while the toughness is reduced. The anhydride type silane coupling agent provided in this application can greatly improve the tensile strength and impact strength of epoxy resin cured product at the same time. This is because the anhydride type silane coupling agent provided in this application, the anhydride is more likely to participate in the curing reaction of epoxy resin, and introduces long side chains, while improving the strength of epoxy resin cured product, improving its toughness.
[0059] Example 6-11 Preparation of modified filler
[0060] Example 6 A modified filler: 50 g of nano-silica was added to 1000 mL of deionized water, and a nanoparticle dispersion was obtained after ultrasonic dispersion. Then 1.5 g of the anhydride silane coupling agent prepared in Example 1 was added, and the stirring speed was maintained at 550 rpm and the temperature was maintained at 70°C. The reaction was carried out for 10 hours to obtain a modified nano-silica solution. The deionized water was removed by rotary evaporation to obtain modified nano-silica.
[0061] Example 7 A modified filler: 50 g of nano-silica was added to 1000 mL of deionized water, and a nanoparticle dispersion was obtained after ultrasonic dispersion. Then 1.5 g of the anhydride silane coupling agent prepared in Example 1 was added, and the stirring speed was maintained at 550 rpm and the temperature was maintained at 70°C. The reaction was carried out for 10 hours to obtain a modified nano-silica solution. The modified nano-silica solution was concentrated to 100 mL by rotary evaporation, purified using a dialysis bag with a molecular weight cutoff of 3000, and finally evaporated to dryness to obtain the modified nano-silica.
[0062] Example 8 A modified filler: 50 g of nano-silica was added to 1000 mL of deionized water, and a nanoparticle dispersion was obtained after ultrasonic dispersion. Then 1.5 g of the anhydride silane coupling agent prepared in Example 2 was added, and the stirring speed was maintained at 550 rpm and the temperature was maintained at 70°C. The reaction was carried out for 10 hours to obtain a modified nano-silica solution. The deionized water was removed by rotary evaporation to obtain modified nano-silica.
[0063] Example 9 A modified filler: 50 g of nano-silica was added to 1000 mL of deionized water, and a nanoparticle dispersion was obtained after ultrasonic dispersion. Then 1.5 g of the anhydride silane coupling agent provided in Example 3 was added, and the stirring speed was maintained at 550 rpm and the temperature was maintained at 70°C. The reaction was carried out for 10 hours to obtain a modified nano-silica solution. The deionized water was removed by rotary evaporation to obtain modified nano-silica.
[0064] Example 10 A modified filler: 50 g of nano-silica was added to 1000 mL of deionized water, and a nanoparticle dispersion was obtained after ultrasonic dispersion. Then 1.5 g of the anhydride silane coupling agent provided in Example 4 was added, and the stirring speed was maintained at 550 rpm and the temperature was 70°C. The reaction was carried out for 10 hours to obtain a modified nano-silica solution. The deionized water was removed by rotary evaporation to obtain modified nano-silica.
[0065] Example 11 A modified filler: 50 g of nano-silica was added to 1000 mL of deionized water, and a nanoparticle dispersion was obtained after ultrasonic dispersion. Then 1.5 g of the anhydride silane coupling agent provided in Example 5 was added, and the stirring speed was maintained at 550 rpm and the temperature was 70°C. The reaction was carried out for 10 hours to obtain a modified nano-silica solution. The deionized water was removed by rotary evaporation to obtain modified nano-silica.
[0066] Example 12-16 Preparation of epoxy floor coating: epoxy resin, modified filler, active diluent, water, additives, curing accelerator and curing agent are mixed and stirred evenly, and the mixture can be directly applied for use.
[0067] The epoxy resin is epoxy resin E-12 and E-44 mixed in a weight ratio of 1:2, the active diluent is benzyl glycidyl ether, specifically active diluent 692, the curing accelerator is 2,4,6-tris(dimethylaminomethyl)phenol, specifically DMP-30, the curing agent is amine curing agent, specifically curing agent DDS, and the additives are leveling agent BYK-306 and defoaming agent BYK-054.
[0068] Example 12: Formulation of wear-resistant epoxy floor coating: 100 parts by mass of epoxy resin, 50 parts by mass of modified filler prepared in Example 6, 5 parts by mass of active diluent, 30 parts by mass of water, 1.5 parts by mass of leveling agent BYK-306, 1.5 parts by mass of defoaming agent BYK-054, 0.5 parts by mass of curing accelerator DMP-30, and 50 parts by mass of curing agent DDS.
[0069] Example 13: Formulation of wear-resistant epoxy floor coating: 30 parts by mass of the modified filler prepared in Example 6 is used, and the rest is the same as in Example 12.
[0070] Example 14: Formulation of wear-resistant epoxy floor coating: 10 parts by mass of the modified filler prepared in Example 6, and the rest is the same as in Example 12.
[0071] Example 15: Formulation of wear-resistant epoxy floor coating: 50 parts by mass of the modified filler prepared in Example 7 is used, and the rest is the same as in Example 12.
[0072] Example 16: Formulation of wear-resistant epoxy floor coating: 50 parts by mass of the modified filler prepared in Example 8 is used, and the rest is the same as in Example 12.
[0073] Comparative Example 1-4 Preparation of Epoxy Floor Coating
[0074] Comparative Example 1 Epoxy floor coating formula: 50 parts by mass of the modified filler prepared in Example 9 is used, and the rest is the same as in Example 12.
[0075] Comparative Example 2 Epoxy Floor Coating Formula: 50 parts by mass of the modified filler prepared in Example 10 is used, and the rest is the same as in Example 12.
[0076] Comparative Example 3 epoxy floor coating formulation: 50 parts by mass of the modified filler prepared in Example 11 is used, and the rest is the same as in Example 12.
[0077] Comparative Example 4 epoxy floor coating formula: 50 parts by mass of unmodified nano-silica filler is used, and the rest is the same as Example 12.
[0078] Performance testing: Mechanical properties of epoxy floor coatings
[0079] After the epoxy floor coatings prepared in Examples 12-16 and Comparative Examples 1-4 were coated and cured, their various technical indicators were tested. The technical indicator requirements refer to GB / T 22347-2018 and the agreed requirements. The test results are shown in Table 2 below.
[0080] Table 2 Mechanical properties of epoxy floor coatings
[0081]
[0082] Referring to the results in Table 2, it can be seen that the water-based epoxy floor prepared in the present application using pure epoxy resin as the substrate has a tensile strength of more than 48 mPa and a wear resistance of ≤0.025, which can meet the standard of super wear resistance.
[0083] Comparing the test results of Examples 12, 13, and 14, it can be seen that modifying the nanoparticles with anhydride-type silane coupling agent can significantly increase the amount of nanoparticles used in the resin, and the mechanical properties of the resulting epoxy floor are improved with the increase in the amount of nanofiller added, especially the wear resistance is significantly improved.
[0084] By comparing the test results of Example 12 and Comparative Examples 1-3, it can be seen that when the amount of nanofiller added is high, the anhydride type silane coupling agent provided in the present application has a better modification effect on nanoparticles than other organic functional group silane coupling agents, and can ensure the uniformity of the dispersion of nanoparticles in the resin system and the high modification effect on the resin system.
[0085] The above is only the preferred implementation of the present application. The protection scope of the present application is not limited to the above embodiments. All technical solutions under the concept of the present application belong to the protection scope of the present application. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present application should also be regarded as the protection scope of the present application.
Claims
1. A wear-resistant epoxy floor coating, characterized in that: It includes component A and component B which are packaged separately and used in a weight ratio of 1:1, wherein component A includes the following components in parts by weight: 100 parts of epoxy resin, 10-50 parts of modified filler, 1-15 parts of active diluent, 10-30 parts of water, and 0-10 parts of additives; component B includes the following components in parts by weight: 50 parts of curing agent; The modified filler is prepared by surface-modifying the filler with an anhydride-type silane coupling agent. The general structural formula of the anhydride-type silane coupling agent is YSi(OR)3, wherein Y is an anhydride group and R is an alkyl group.
2. The wear-resistant epoxy floor coating according to claim 1, characterized in that: In the general structural formula of the anhydride type silane coupling agent, Y is a maleic anhydride group, and the anhydride type silane coupling agent is obtained by a pericyclic reaction of maleic anhydride and α-alkenyl silane.
3. The wear-resistant epoxy floor coating according to claim 2, characterized in that: The specific preparation steps of the anhydride type silane coupling agent are: mixing maleic anhydride and α-alkenyl silane, maintaining the mixture at a certain reaction temperature for a certain time, and then separating and purifying the mixture to obtain the anhydride type silane coupling agent.
4. The wear-resistant epoxy floor coating according to claim 3, characterized in that: The α-alkenyl silane includes but is not limited to acryltrimethoxysilane, acryltriethoxysilane, isobutylenyltrimethylsilane, 5-hexenyltrimethoxysilane and the like.
5. The wear-resistant epoxy floor coating according to claim 3, characterized in that: During the preparation of the anhydride silane coupling agent, the heating reaction temperature is 180-200° C. and the heating reaction time is 8-16 hours.
6. The wear-resistant epoxy floor coating according to claim 1, characterized in that: The specific preparation steps of the modified filler are: using water as a solvent to prepare a nanoparticle dispersion, mixing the nanoparticle dispersion with an anhydride type silane coupling agent, heating and reacting for a period of time, and then separating and purifying to obtain the modified filler.
7. The wear-resistant epoxy floor coating according to claim 6, characterized in that: The amount of the anhydride silane coupling agent used is 1-3 wt % of the nanoparticles.
8. The wear-resistant epoxy floor coating according to claim 6, characterized in that: The crude product of the reaction can be directly freed of solvent to obtain the finished product; or, it can be first concentrated and then purified using a dialysis bag, and finally evaporated to dryness by rotary evaporation to obtain the finished product.
9. The wear-resistant epoxy floor coating according to claim 1, characterized in that: The epoxy resin is composed of E-12 and E-44 mixed in a weight ratio of 1:(2-3).
10. A method for preparing the wear-resistant epoxy floor coating according to any one of claims 1 to 9, characterized in that: During preparation, components A and B are prepared and packaged separately, and are mixed and stirred evenly in a weight ratio of 1:1 when used. The preparation method of component A is as follows: epoxy resin, modified filler, active diluent, water and additives are mixed and stirred evenly to obtain the product.
Citation Information
Patent Citations
Epoxy resin wave absorbing composite material and preparation method thereof
CN109135184A
Maleic anhydride and silane coupling agent copolymer compatilizer, preparation method and application thereof
CN110498888A
Waterborne epoxy floor coating and preparation method thereof, and construction method of waterborne epoxy floor coating
CN110885615A
High-performance anti-ozone environment-friendly anticorrosive coating and preparation method thereof
CN112898875A
FR1572851A